Relevance of Sampling Techniques in Medical Research - Sathian, Brijesh; Sreedharan, Jayadevan; Roy, Bedanta; Banerjee, Indrajit; Supram, Hosuru Subramanya (Journal of Biomedical Sciences, 2015)
It is the era of developments and technologies in Southeast Asian countries including Nepal. Medical practice is growing to its supreme level. There is several funded and clinically relevant research works from this region. But it is questionable whether the data is collected scientifically and the inferred evidence is useful to the medical sciences. Improper sampling methods will result with biased evidence, which will make the researcher misleading. This article will discuss the basic sampling techniques required for a good research. DOI: http://dx.doi.org/10.3126/jbs.v2i1.13031 Journal of Biomedical Sciences 2015 Mar.; 2(1): 3-6